(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Vitamin D has received considerable interest from the medical community and the public because of recent evidence for the nonskeletal effects of vitamin D combined with the finding of widespread global deficiency. It has been estimated that almost 1 billion people worldwide suffer from vitamin D deficiency or insufficiency. In addition, neurobiological and neuroendocrinological substrates have been identified that indicate a link between hypovitaminosis D and several psychiatric conditions, including depression. Objectives: This study aimed to assess vitamin D level in patients with depressive disorders and to compare it with normal individuals. Materials & Methods: This cross-sectional type of comparative study was carried out in the Department of Physiology, Rajshahi Medical College, Rajshahi, in collaboration with the outpatient department of Psychiatry Rajshahi Medical College Hospital over 12 months from January 2019 to December 2019 among the Depressive patients and healthy individuals to find out and compare the vitamin D level between the two groups. Approval from the Ethical Review Committee (ERC) was obtained before the commencement of the study. A pA pre-designed, validated, structured questionnaire was used to gather information from 108 respondents by purposive sampling. Out of the 54 were newly diagnosed depressive patients, and 54 were healthy persons. In addition, a blood sample was collected to measure 25(OH)D level, and all values were analyzed statistically. Results: The Result showed a significant difference in mean plasma 25(OH)D level between the patients with depressive disorder and the healthy individuals. Circulating 25(OH)D level was found to be significantly low in the group of patients with depression. Conclusion: The present study demonstrated a significant correlation between hypovitaminosis D in patients with depressive disorders. It is suggested that possible factors such as hypovitaminosis D should be done as a routine investigation to reduce the incidence of depression. Furthermore, vitamin D supplementation might be a complementary treatment for depression. TAJ 2022; 35: No-2: 159-168